The importance of wild plant species as potential inoculum reservoirs of white root rot disease. Issue 1 (24th July 2013) - Takemoto, S.; Nakamura, H.; Tabata, M.; Woodward, S.
Summary Rosellinia necatrix is a soilborne plant pathogenic fungus belonging to the phylum Ascomycota. The fungus is distributed widely in temperate zones and often causes huge economic losses on numerous crop plants. To determine the potential for wild plants to serve as inoculum reservoirs of white root rot disease, eight woody and two herbaceous plant species belonging to nine families were inoculated with two R. necatrix isolates. The species used were Actinidia polygama, Broussonetia kazinoki, Camellia sinensis, Castanea crenata, Hydrangea serrata, Magnolia obovata, Pteridium aquilinum, Petasites japonicus, Quercus serrata and Rosa multiflora, all common flora in the cool temperate forests of Japan. The mortality of plants varied between species, independent of the effect of fungal isolates. Although some of the plants survived fungal infection, all plant species tested were more or less susceptible, having rotting lesions on the inner bark and cortex. For the woody plants, most of the mycelial strands in the diseased tissues became plumose mycelia, growing compressed between the outer and inner barks. However, mycelia found in diseased tissues of the two herbaceous plants were not in the form of plumose mycelia. All plant species harboured mycelial strands on the surface of their root systems and underground main stem, and the amount of the mycelial strands did not correlate with the mortality of the plants. Even if plants exhibited no external symptoms, some of them harboured abundant mycelial strands. In conclusion, wild plants can serve as alternative host plants for R. necatrix and function as persistent inoculum reservoirs, irrespective of their apparent health status. Thus, assessments of such latent host plants must be considered in the course of managing white root rot.